Reproductive tract microbiome dysbiosis associated with gynecological diseases - Qingyue Zheng; Qingyue Zheng; Tianshu Sun; Xiaochuan Li; Xiaochuan Li; Lan Zhu; Lan Zhu (Frontiers in Cellular and Infection Microbiology)
Female health and the microbiota of the reproductive tract are closely associated. The research scope on reproductive tract microbiota extends from the vaginal to the upper reproductive tract and from infectious diseases to various benign and malignant gynecological and obstetrical diseases. The primary focus of this paper was to evaluate the most recent findings about the role of reproductive tract microbiota in gynecological diseases, including endometrial polyps, uterine fibroids, endometriosis, adenomyosis, endometrial hyperplasia, and endometrial carcinoma. Different stages of gynecological diseases have diverse microbiota in the female reproductive tract, and some specific bacteria may help the disease progress. For example, Fusobacterium may exacerbate endometriosis, while treatments that target microbiota, such as antibiotics, probiotics, and flora transplantation, showed some efficacy in the experiment. These findings indicate the wonderful prospect of this field. Additionally, we have discussed how microbiome research can improve our understanding of the interactions between reproductive tract microorganisms and hosts, aid in the screening and diagnosis of gynecological diseases, and direct the development of preventive and therapeutic strategies aimed at maintaining and restoring a healthy reproductive tract microbiota when combined with other technologies like transcriptome and proteome, in vitro cultured cells, and animal models.